2019
DOI: 10.1145/3359223
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential for Technology to Improve Cystic Fibrosis Care Provision

Abstract: Health care systems increasingly promote self-management of chronic conditions outside of traditional clinical environments, often through technologies which help to support patient self-care and engagement with medical professionals. We investigate specialist care provision in cystic fibrosis (CF), a life-shortening genetic condition, to understand the experiences of those living with it and of professionals who provide such care. Our work highlights how the motivations for the use of technology in this conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…15 Still, telehealth has been investigated in the context of CF care as a way to enhance convenience, decrease cost, fill gaps in access due to geography, and increase the frequency of monitoring to improve patient satisfaction and outcomes. 16,17 The few studies investigating patient experience with telehealth have demonstrated high satisfaction and good uptake, indicating this to be a feasible option for patients. 18,19 A recent review determined telehealth services generally to be equivalent to in-person care in most disciplines, 20 and although there is a need for more longitudinal comparative studies, specialty teleconsultation services have demonstrated equivalence to face-toface patient care during the COVID-19 pandemic.…”
Section: Impact Of Covid-19 On Cf Center Carementioning
confidence: 99%
“…15 Still, telehealth has been investigated in the context of CF care as a way to enhance convenience, decrease cost, fill gaps in access due to geography, and increase the frequency of monitoring to improve patient satisfaction and outcomes. 16,17 The few studies investigating patient experience with telehealth have demonstrated high satisfaction and good uptake, indicating this to be a feasible option for patients. 18,19 A recent review determined telehealth services generally to be equivalent to in-person care in most disciplines, 20 and although there is a need for more longitudinal comparative studies, specialty teleconsultation services have demonstrated equivalence to face-toface patient care during the COVID-19 pandemic.…”
Section: Impact Of Covid-19 On Cf Center Carementioning
confidence: 99%